Perancangan Sistem Monitoring Surat Perintah Perjalanan Dinas dengan Mobile App Android untuk Biro Kepegawaian Universitas Nurul Jadid - Fathorazi Nur Fajri; M. Noer Fadli Hidayat; Suci Rahayu Agustini (GUYUB: Journal of Community Engagement, 2020)
An official travel warrant is a letter made for employee who has been assigned for an official trip to a certain area. The application process of The official travel warrant (surat perintah perjalanan dinas/SPPD) at Nurul Jadid University involves the Faculty Administration by submitting it to Head of Administration and the one who who has a right for approval, such as Representative Rector. The current process is still based on the old system and has an impact on long synchronization between employees due to lack of coordination and time-delays in the process of submitting service processes. Therefore, this study is intended to offer a system design for monitoring official travel orders with the Android Mobile App at Nurul Jadid University. The method used in this research is the waterfall method, whose stages or paths run from top to bottom. The target of this research is the monitoring of official trips which will make it easier for all parties. The results of this study are 96.9% of employees said that this system really helps the process of official travel effectively and efficiently.